Gatekeeping and the utilization of physician services in France: Evidence on the Médecin traitant reform. Issue 6 (June 2017) - Dumontet, Magali; Buchmueller, Thomas; Dourgnon, Paul; Jusot, Florence; Wittwer, Jérôme
Highlights: We evaluate the effect of a gatekeeping reform in France. The analysis is based on a mix of administrative claims and survey data. After the reform went into effect, specialist visits fell slightly. Self-referred visits and the number of different GPs seen also declined. Abstract: In 2005, France implemented a gatekeeping reform designed to improve care coordination and to reduce utilization of specialists' services. Under this policy, patients designate a médecin traitant, typically a general practitioner, who will be their first point of contact during an episode of care and who will provide referrals to specialists. A key element of the policy is that patients who self-refer to a specialist face higher cost sharing than if they received a referral from their médecin traitant . We consider the effect of this policy on the utilization of physician services. Our analysis of administrative claims data spanning the years 2000–2008 indicates that visits to specialists, which were increasing in the years prior to the implementation of the reform, fell after the policy was in place. Additional evidence from the administrative claims as well as survey data suggest that this decline arose from a reduction in self-referrals, which is consistent with the objectives of the policy. Visits fell significantly both for specialties targeted by the policy and specialties for which self-referrals are still allowed for certain treatments. This apparent spillover effect may suggest that, at least initially, patients did not understand the subtleties of the policy.